(untitled) (University Heart Journal, 2018)
Stress echocardiography (SE) is an established technique for the assessment of extent and severity of coronary artery disease. The combination of echocardiography with a physical, pharmacological or electrical stress allows to detect myocardial ischemia with an excellent accuracy. A transient worsening of regional function during stress is the hallmark of inducible ischemia. In recent years, SE has become an established method for the assessment of a wide spectrum of challenging clinical conditions, including systolic or diastolic heart failure, non-ischaemic cardiomyopathy, valvular heart disease, pulmonary hypertension (PH), athletes’ hearts, congenital heart disease (CHD) and heart transplantation. Advantages of SE include the ubiquitous availability of echocardiography, lack of ionising radiation, choice of physiological or pharmacological stressors, good diagnostic accuracy and robust supporting evidence base. SE has evolved significantly as a technique over the past three decades and has benefitted considerably from improvements in overall image quality (superior resolution), machine technology (e.g. digital cine-loop acquisition and side-by-side image display) and development of second-generation ultrasound contrast agents that have improved reader confidence and diagnostic accuracy. SE provides similar diagnostic and prognostic accuracy as radionuclide stress perfusion imaging or magnetic resonance, but at a substantially lower cost, without environmental impact, and with no biohazards for the patient and the physician. A paradigm shift will occur when from a highly expertise qualitative reading SE will move to a quantitative approach that would make it easier also for less skilled readers. Technological premises are there at hand but they have not reached a full-blown status to be used on a routine clinical basis. Society recommendations and guidelines are mostly based on consensus and level of evidence C. The gap of knowledge should be filled with prospective large scale studies to support evidence-based treatment strategies. The purpose of this article is to review the breadth of SE in contemporary clinical cardiology. University Heart Journal Vol. 14, No. 1, Jan 2018; 31-37